The story of the Salem witch trials: "we walked in clouds and could not see our way" - Le Beau, Bryan F. (Routledge, Taylor & Francis Group, 2023)
"Providing an accessible and comprehensive overview, The Story of the Salem Witch Trials explores the events between June 10 and September 22, 1692, when nineteen people were hanged, one was pressed to death and over 150 were jailed for practicing witchcraft in Salem, Massachusetts. This book explores the history of that event and provides a synthesis of the most recent scholarship on the subject. It places the trials into the context of the Great European Witch-Hunt and relates the events of 1692 to witch-hunting throughout seventeenth century New England. Now in a third edition this book has been updated to include an expanded section on the European origins of witch hunts, an updated and expanded epilogue which discusses the witch hunts, real and imagined, historical and cultural, since 1692 and an extensive list of internet resources, sources of primary documents, documentaries, movies, artwork, and resources that may be used in the classroom or for further study. This complex and difficult subject is covered in a uniquely accessible manner that captures all the drama that surrounded the Salem witch-trials. From beginning to end, the reader is carried along by the author's powerful narration and mastery of the subject. While covering the subject in impressive detail, Bryan Le Beau maintains a broad perspective on the events, and wherever possible, lets the historical characters speak for themselves. Le Beau highlights the decisions made by individuals responsible for the trials that helped turn what might have been a minor event into a crisis that has held the imagination of students of American history. The Story of the Salem Witch Trials 3rd edition is essential for students and scholars alike interested in Women's & Gender History, Colonial American History, and Early Modern History"--